Bangladesh - Revenue Mobilization Program for Results: VAT Improvement Program Technical Assessment - World Bank (Washington, DC, 2014)
This operation will support the VAT Improvement Program to assist the National Board of Revenue (NBR) in streamlining and modernizing Value Added Tax (VAT) operations and establishing an integrated VAT Management System for the purposes of implementing the new regime. The primary focus of the program is to prepare the administration to be able to administer the new VAT, which is to be introduced in July 2015. The new VAT Act, 2012 provides for a modern VAT scheme based on few exemptions and self-assessment. The Act provides the legal basis for the new VAT administration, and the impetus for a shift from manual to automated and modernized core tax business processing. The program is part of the government s broader tax reform agenda as articulated in the Tax Modernization Plan 2011-16 (endorsed by Parliament in June 2011), which envisages policy and institutional reform alongside a program for automating NBR operations to improve services to taxpayers, reduce administrative costs for taxpayers, and improve compliance. The VAT improvement program aims to widen the tax base by enhancing voluntary compliance, and reducing non-compliance. The ultimate goals are to increase VAT revenues and enhance the transparency of the VAT administration in Bangladesh in order to achieve its medium-term revenue target of a tax-to GDP-ratio of 12.2 percent by FY 2016; and to enhance the VAT compliance. Towards this objective, the program will also address those structural weaknesses embedded in the tax system that result in skewed tax bases and provide wide opportunities for evasion and corruption. Importantly, the VAT improvement program will support the strategic reform agenda, also supported by the IMF s Extended Credit Facility to enable NBR to fully implement the new VAT law.